Referral letters in oral medicine: standard versus non-standard letters - Navarro, Cláudia Maria [UNESP]; Miranda, IAN; Onofre, Mirian Aparecida [UNESP]; Sposto, M. R. (Churchill Livingstone, 2002)
Usually referral letters are the only means of communication between general practitioners and specialists in the health area. However, they are inadequate if important basic data are omitted. The aim of this study was to compare the content of standard and non-standard letters. A total of 1956 files from the Oral Medicine Service were consecutively evaluated (March 1996 to September 2000). Key items were considered for analysis and the results were stored in a database using the Epinfo 6.04 program. The X-2 test (a=0.05) was applied to the results. of the 1956 files examined, 34% (662) had a referral letter, 31% of them being standard letters and 69% non-standard letters. Most standard letters (87%) were from professionals of public health institutions. Most percent discrepancies between standard and non-standard letters were observed for patient address (14.90 vs 1.32%), patient age (54.81 vs 9.47%), chief complaint (32.21 vs 8.37%), fundamental lesion (29.33 vs 13.66%), and symptoms (27.81 vs 15.42%,,). Statistically significant differences were observed for patient age, professional referring the patient, chief complaint, and site of the lesion. The quality and quantity of the information differed significantly between the two types of letters. The standard letters were more complete and contained information commonly absent in the non-standard letters. We suggest the use of standard letters for improving the quality of communication among professionals.
Keywords: referral letters; dentist; oral medicine; standard letters; comparison